The Influence of First‐Hand Testimony and Hearsay on Children's Belief in the Improbable. Issue 4 (24th April 2017) - Lane, Jonathan D.; Ronfard, Samuel; El‐Sherif, Diana
Abstract : Children (3.5–8.5 years; n = 105) heard claims about the occurrence of improbable or impossible events, then were asked whether the events could really happen. Some claims were based on informants' first‐hand observations and others were hearsay. A baseline group ( n = 56) reported their beliefs about these events without hearing testimony. Neither first‐hand claims nor hearsay influenced beliefs about impossible events, which remained low across the age range. Hearsay (but not first‐hand claims) did influence beliefs about improbable events. Preschoolers expressed greater belief following hearsay, compared to their beliefs following first‐hand claims and compared to the baseline group's beliefs. By contrast, older children expressed less belief following hearsay, compared to their beliefs following first‐hand claims and compared to the baseline group's beliefs.